(Novels) Idiom , evolution and properties in the light of critic Shugaa Muslim Al-Aani - داود سلمان العنبكي سولاف مصحب مهدي (College of Education for Women, 2019)
A critics ,Shugaa Muslim Al-Aany, has specific critical principles in his branch classifications for the type of the novel that is linked with its sources and what is adopted of critical approaches and curriculums. The novel by its type as a literary one has occupied Al-Any's critical importance very much ,he has divided it historically according to its historical development ,the impact of dr.Abd Al-Muhassen Tha Badr's divisions on Al-Any cannot hidden. In his speech about the origin of novel and story art generally , Al-Any becomes between the acknowledgement of the affect of Al-Mgma in rising of this art and denied its affect at last. He has classified the novel also as a stylistic classification:(an impressionist novel);(A novel of current of consciousness);( a novel of time density),(a scene novel);(Al- Musrwah);(a monologue novel) or(a novel of the one sound);(polyphone)or (polyphonies) ;( a novel of Narcissistic structure) .Besides ,he depends on the social and philosophical principles when he has classified the novel into (the old social novel)and (the new dramatic novel).The one can see confusion in his classifications of the novel (Jalel Khaled),he has classified it as the first artistic analytical novel ,a romantic one once , an educational in another time, But the critics realize that this confusion that fall within it ,so he restudies it for decades to prove that it is a intellectual acculturation and rearing although it violates in its art other novels of the same generation.